2017
DOI: 10.1111/cbdd.12968
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, antimalarial activity in vitro, and docking studies of novel neolignan derivatives

Abstract: The absence of effective vaccines against malaria and the difficulties associated with controlling mosquito vectors have left chemotherapy as the primary control measure against malaria. However, the emergence and spread of parasite resistance to conventional antimalarial drugs result in a worrisome scenario making the search for new drugs a priority. In the present study, the activities of nine neolignan derivatives were evaluated as follows: (i) against blood forms of chloroquine-resistant Plasmodium falcipa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…As an analogue of neolignane, ester S51 ( Fig. 11) was identified and measured the antimalarial activity in vitro [70]. The result revealed that S51 exhibited moderate antimalarial activity against blood forms of chloroquine-resistant P. falciparum with both the IC 50 values for 3 H-hypoxantine and HRPII were 127.9 mM.…”
Section: Synthetic Tmca Esters As Antimicrobial Agentsmentioning
confidence: 99%
“…As an analogue of neolignane, ester S51 ( Fig. 11) was identified and measured the antimalarial activity in vitro [70]. The result revealed that S51 exhibited moderate antimalarial activity against blood forms of chloroquine-resistant P. falciparum with both the IC 50 values for 3 H-hypoxantine and HRPII were 127.9 mM.…”
Section: Synthetic Tmca Esters As Antimicrobial Agentsmentioning
confidence: 99%
“…9 and 10) showed significant in vitro activity with no cytotoxicity effects. For the molecular docking results, the investigators demonstrated that both derivatives effectively occupied cavities S1 and S2 in FP-2 [146] . Coumarin containing pyrazoline derivatives were also synthesized.…”
Section: E] Herbal Inhibitors 1 Sole Inhibitors For Fpsmentioning
confidence: 99%